(untitled) (Damascus University Journal for legal sciences, 2025)
Repatriation criteria have developed as a durable solution to refugee crises, In the context of state practices and UNHCR policies. Given the international community focusing on voluntary repatriation as a preferred solution since the 1990s, Many legal and political debates have arisen about the criteria for voluntary, safe and dignified return, In terms of their legal basis, normative scope, and conceptual content. Moreover, These criteria encountered multiple problems that led to the erosion of voluntariness - despite the fact that it is the bold legal principle that puts an end to the fraudulent ways to prefer the interests of states over the rights of refugees - as well as safety and dignity, which are the central elements to restore the nexus of citizenship, and to achieve the sustainable return.